2020
DOI: 10.3390/cells9020510
|View full text |Cite
|
Sign up to set email alerts
|

Lactate in Sarcoma Microenvironment: Much More than just a Waste Product

Abstract: Sarcomas are rare and heterogeneous malignant tumors relatively resistant to radio- and chemotherapy. Sarcoma progression is deeply dependent on environmental conditions that sustain both cancer growth and invasive abilities. Sarcoma microenvironment is composed of different stromal cell types and extracellular proteins. In this context, cancer cells may cooperate or compete with stromal cells for metabolic nutrients to sustain their survival and to adapt to environmental changes. The strict interplay between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 170 publications
0
14
0
Order By: Relevance
“…In addition, an increased level of lactate dehydrogenase-A (LDH-A) was observed in CHS [ 59 ], which contributes to its treatment resistance [ 21 ]. In CHS, high expression of amphiregulin was also found, a ligand for epidermal growth factor receptor (EGFR), and correlates with histological grading in CHS [ 44 ].…”
Section: Morphology and Differentiation Of Chondrosarcomamentioning
confidence: 99%
“…In addition, an increased level of lactate dehydrogenase-A (LDH-A) was observed in CHS [ 59 ], which contributes to its treatment resistance [ 21 ]. In CHS, high expression of amphiregulin was also found, a ligand for epidermal growth factor receptor (EGFR), and correlates with histological grading in CHS [ 44 ].…”
Section: Morphology and Differentiation Of Chondrosarcomamentioning
confidence: 99%
“…With the increase of exogenous lactate concentration, the expression of KLHDC8A was gradually increased (Figure 7A). In the tumour microenvironment, lactate accumulation was a result of increased glycolysis 29 . We want to know whether glycolysis was correlated with KLHDC8A expression levels.…”
Section: Resultsmentioning
confidence: 99%
“…In the tumour microenvironment, lactate accumulation was a result of increased glycolysis. 29 We want to know whether glycolysis was correlated with KLHDC8A expression levels. As expected, the glioma cells stimulated with gradient concentrations of glucose (0-4.5 mg/mL) showed a significant increase in the expression of KLHDC8A ( Figure 7B).…”
Section: Lactate and Glucose Induce Klhdc8a Expression In Glioma Cellsmentioning
confidence: 99%
“…Various studies have reported that they may sustain tumor progression by inhibiting T cell proliferation and activation, suppressing the cytotoxic activity of NKs, redirecting macrophages towards the immunosuppressive M2 phenotype and promoting regulatory T cell differentiation. In addition, MSCs inhibit B cell proliferation and antibody production 151 .…”
Section: Barriers To Immunotherapy For Soft Tissue and Bone Sarcomamentioning
confidence: 99%